Determinants of drought risk coping mechanisms among the farmers of Northern region of Bangladesh: Drought risk coping mechanisms - Farid, Kazi Shek; Tanny, Nishith Zahan; Rahman, Md Wakilur (Journal of the Bangladesh Agricultural University, 2019)
Drought is a major constraint on agricultural production and livelihood in the north-western region of Bangladesh. An understanding of the effects of drought and farmers’ coping mechanisms is essential in designing technological and policy interventions for effective drought mitigation. The current study investigates the impacts of drought, examines farmers’ coping strategies for drought induced crop failure and the determinants of their mechanism choices by employing both quantitative and qualitative approach. Multiple data sources, including semi-structured interview survey with 218 randomly selected farmers; and four focus group discussions with farmers, local leaders, NGO workers, and government officials were used to capture various aspects of drought risks and coping practices. ‘Multinomial logit’ model was adopted to analyze the factors affecting the decision of coping strategies in response to drought. Results of farm household survey data indicates that the respondents experienced 3.15 droughts on an average in last five years which affected about 15 percent of their crop land and resulted more than 17 percent crop loss per year. Focus group discussions confirm that farmers followed various traditional ex ante and ex post coping strategies in order to avoid crop loss and minimize livelihood constraints. The coping mechanisms mostly adopted by farmers among others were borrowing money, cultivating less water consuming crops and cutting meals. Findings of multinomial logistic regression model reveal that the environment determinant of the choices of coping options was frequency of drought and main socio-economic determinants of coping choices were crop loss due to drought and land holding systems. J. Bangladesh Agril. Univ. 17(1): 58–64, March 2019